NEUROTOXINS FROM INVERTEBRATES AS ALTERNATIVE THERAPEUTIC AGENTS AND TOOLS IN BASIC RESEARCH - PEREAÑEZ, Jaime A.; VARGAS, Leidy J. (Vitae, 2009)
Animal venoms are a complex mixture of proteins, peptides, enzymes and trace elements such as carbohydrates and salts, which aim to immobilize the prey and begin digestion. Toxins are isolated substances from venons, with one or more specific actions on victims. Many of these compounds have action on specific receptors located on the central and/or peripheral nervous system, while others exert their effects by acting on other proteins. Since the discovery in 1971 of the peptide that gave rise to Captopril and the fact that a lot of toxins are useful as tools for physiological process studies, animal venoms began to be watched as sources rich in bioactive compounds and its potential use as therapeutic agents is now considered. There are now different drugs and diagnostic or basic investigation tools derivated from toxins. This review based on publications from the last 10 years pretends to provide a current view of the use of some of these molecules as tools in different fields of biomedicine and pharmacy, and in the application of these as new alternative therapeutic agents or as models in designing them.